Tranformasi Dakwah Melalui Media Sosial di Yayasan Khadimul Ummah Kajang Kabupaten Bulukumba - Ariadi; Firdaus Muhammad; Hamriani (Jurnal Diskursus Islam, 2026)
This study examines the transformation of da’wah through the use of social media at the Khadimul Ummah Foundation in Kajang, Bulukumba Regency, as a response to developments in digital technology. The research approach employs a descriptive qualitative method with a sociological perspective, utilizing observation, interviews, and documentation. The results indicate that the foundation has developed a hybrid da’wah model that combines traditional methods with social media platforms such as Instagram, Facebook, YouTube, and TikTok. The use of digital platforms has expanded the reach of da’wah, increased interaction with the community, and strengthened the image of the Islamic educational institution. Dakwah content is presented in the form of short videos, motivational messages, and documentation of religious activities. Despite facing limitations in human resources and facilities, digital dakwah remains effective through internal collaboration. This transformation demonstrates the pesantren’s strategic adaptation to the digital era without abandoning the traditional values of Islamic dakwah.